Perspectivas e desafios na gestão escolar de tempo integral - Braga, Keila Francisca (Universidade Federal do Tocantins, 2019)
This study aimed to analyze the perspectives and challenges of managing full-time education and its implications in the actions of managers of the Sunflower State School of Combined-TO, thus considering the importance of school management in the Democratic sphere, Participatory. This study was founded by theorists who embroidered on the theme presenting, such as: Paro (2001), Ferreira (2003), Bastos (2002), Barros (2002), Luck (2001), Davis (2002), Dourado (2003). The methodology approached is a qualitative research, with case study and application of a questionnaire directed to the pedagogical coordinator, manager, parents and students. With This, it was found that the challenges range from infrastructure to low investments to improve the quality of education.